Polyphosphates and Complement Activation - Conway, Edward M. (Frontiers in Medicine, 2019)
To sustain life in environments that are fraught with risks of life-threatening injury, organisms have developed innate protective strategies such that the response to wounds is rapid and localized, with the simultaneous recruitment of molecular, biochemical and cellular pathways that limit bleeding and eliminate pathogens and damaged host cells, while promoting effective healing. These pathways are tightly regulated, as their over- or under-activation may lead to inadequate healing, disease, and/or demise of the host. Recent advances in our understanding of coagulation and complement, a key component of innate immunity, have revealed critical molecular links that regulate the delicate balance of both systems, thereby providing the necessary elements to achieve homeostasis. Polyphosphate is one such factor that intriguingly, plays a key role by promoting coagulation, while dampening complement activation, a discovery that is uncovering novel insights into mechanisms underlying disease and new therapeutic strategies.